Emerging Market Economies and Financial Globalization Argentina, Brazil, China, India and South Korea - Stanley, Leonardo (Anthem Press, 2017)
In the past, foreign shocks arrived to national economies mainly through trade channels, and transmissions of such shocks took time to come into effect. However, after capital globalization, shocks spread to markets almost immediately. Despite the increasing macroeconomic dangers that the situation generated at emerging markets in the South, nobody at the North was ready to acknowledge the pro-cyclicality of the financial system and the inner weakness of "decontrolled" financial innovations because they were enjoying from the "great moderation." Monetary policy was primarily centered on price stability objectives, without considering the mounting credit and asset price booms being generated by market liquidity and the problems generated by this glut. Mainstream economists, in turn, were not majorly attracted in integrating financial factors in their models. External pressures on emerging market economies (EMEs) were not eliminated after 2008, but even increased as international capital